Internalisasi Nilai-Nilai Al-Qur’an Berbasis Deep Learning Dalam Pengembangan Karakter Religius Anak Autisme - Hafizhatul Munawwarah; M. Ihsan Fauzi; Asiah Asiah (Early Stage, 2026)
The development of religious character in children with autism within inclusive Early Childhood Education (ECE) settings faces a fundamental challenge: the dominance of verbal and symbolic approaches to learning Quranic values, whereas children with autism require concrete, structured, and experiential approaches. This article aims to construct a theoretical framework for the internalization of Quranic values based on the deep learning approach, that is, meaningful learning that emphasizes active engagement, deep conceptual understanding, and the connection between experience and real life, as a strategy for developing the religious character of children with autism in inclusive ECE settings. This study employs a systematic literature review that integrates the theory of value internalization. (Lickona, 2019) The deep learning approach in education (Fullan et al., 2018), and the principles of Quran-based inclusive Islamic education. The findings of this review indicate that the internalization of Quranic values in children with autism can be structured into three continuous stages: concrete value introduction, habituation through structured routines, and consistent reinforcement of religious behavior. This framework affirms the central role of educators as role models (Uswah Hasanah) and a supportive learning environment as key determinants of successful value internalization. This article contributes to the development of inclusive Islamic education, particularly in designing religious value learning models that are adaptive and responsive to the needs of children with autism.